Обмеження здійснення особистих немайнових прав юридичних осіб під час введення воєнного стану - Попова, С. О.; Popova, S. O.; Попова, В. А.; Popova, V. A. (Європейські перспективи. - 2023. - №3. - С. 103-110, 2023)
Визначено правові аспекти обмеження особистих немайнових прав юридичних осіб. Встановлено, що початок повномасштабного вторгнення рф на територію України зумовив запровадження спеціального правового режиму воєнного стану, який встановлює певні обмеження здійснення прав осіб. Проаналізовано законодавство та нормативні положення, які регламентують діяльність юридичних осіб та їх працівників під час збройного конфлікту рф проти України та визначають порядок дій у випадку, якщо ці обмеження стосуються безпосереднього провадження їх професійної діяльності. Детально розглянуто обмеження таких особистих немайнових прав юридичних осіб, як право на діяльність, право на вільний вибір місцезнаходження, право на інформацію, право на таємницю кореспонденції, право на найменування та право на конкуренцію.

The article defines the legal aspects of restricting personal non-property rights of legal entities. It has been studied that the restricting of basic rights is carried out both by direct prohibitions and by removing one or another authority from the content of a specific right, as well as by establishing a special procedure for the implementation of such a right. It was analyzed and determined that restrictions on the exercise of personal non-property rights of legal entities during the war are poorly researched. It was established that the beginning of the Russian’s full-scale military invasion of Ukraine led to the introduction of a special legal regime of martial law, which establishes certain restrictions on the exercise of the rights of individuals. The legislation of Ukraine was analyzed - the Decree of the President of Ukraine dated February 24, 2022 “On the imposition of martial law in Ukraine”, the Law of Ukraine “On the Legal Regime of Martial Law”, the Law of Ukraine “On Information”, the Law of Ukraine “On Media”, and other related normative provisions that regulate the activities of legal entities and their employees during the armed conflict of the Russian Federation against Ukraine and determine the procedure for actions in the event that these restrictions concern the direct conduct of their professional activities. The restrictions of such personal non-property rights of legal entities as the right to activity, the right to free choice of location, the right to information, the right to secrecy of correspondence, the right to name and the right to competition are considered in detail. It was established that despite the guarantees of freedom of expression, restrictions on the right to information, which were introduced to protect national security and people’s lives and health, are in place during the implementation of martial law in Ukraine. It has been proven that the established restrictions on the exercise of personal non-property rights of legal entities play a positive role, because they help establish any illegal actions and prevent them.

Определены правовые аспекты ограничения личных неимущественных прав юридических лиц. Установлено, что начало полномасштабного вторжения России на территорию Украины обусловило введение специального правового режима военного положения, устанавливающего определенные ограничение осуществления прав лиц. Подробно рассмотрены ограничения таких личных неимущественных прав юридических лиц, как право на деятельность, право на свободный выбор местонахождения, право на информацию, право на тайну корреспонденции, право на наименование и право на конкуренцию.
Restrictions on the exercise of personal non-property rights of legal entities during the imposition of martial law
Keywords: особисті немайнові права; personal non-property rights; личные неимущественные права; обмеження прав; limitation of rights; ограничение прав; юридична особа; legal entity; юридическое лицо; воєнний стан; martial law; военное положение; обмеження права на діяльність; restriction of the right to activity; ограничение права на деятельность; законодавство; legislation; законодательство